MANFAAT KEGIATAN EKSTRAKURIKULER MUHADHOROH DALAM PENEGENGEMBANGAN SOFT SKILL SISWA DI MADRASAH ALIYAH AL-MU’MIN MUHAMMADIYAH TEMBARAK (ALMATERA) - Safriyan Mifta Anna Fatakun; Abdul Malik (As-Sulthan Journal of Education, 2025)
This study aims to find out the benefits of extracurricular activities of Muhadhoroh in the development of students' soft skills at MA Al-Mu'min Muhammadiyah Tembarak Temanggung (ALMATERA). Likewise, to be able to find out the factors that affect these activities, both supporting and inhibiting factors. The method used in this study is qualitative and descriptive-based. Data is obtained through observation or direct observation of the course of Muhadhoroh activities and digging up information from sources who can provide more indepth information, then the third is a documentation study to obtain data used by supporters from official documentation sources of madrasah. Then the data obtained is processed with the initial stage of filtering the data, then the data is displayed in the form of a narrative to facilitate the reader's understanding, and the last is to draw conclusions from what has been the findings in this study. The results of the study show that the activities of Muhadhoroh at MA ALMATERA students carry out every Thursday night, participants who perform based on the schedule that has been made by the supervisor/person in charge of this activity, there are three parts, namely some are in charge of being the host, some are delivering lectures, and some are playing roles. The inhibiting factors are the lack of confidence from students, and dense activities that result in students being tired. The driving factor is motivation from teachers, and support from both facilities and infrastructure from the foundation. The benefit of this activity is that students' soft skills are increasingly developing such as being more confident in appearing in public, and students after graduation are ready to engage in da'wah in the community, which is also beneficial for madrasas because they can provide more value than other schools/madrasas.